The Role of the Two-Component System PhoP/PhoQ in Intrinsic Resistance of Yersinia enterocolitica to Polymyxin - Guo, Haoran; Zhao, Tong; Huang, Can; Chen, Jingyu (Frontiers in Microbiology, 2022)
Polymyxin is the “last-resort” of antibiotics. The self-induced resistance to polymyxin in gram-negative bacteria could be mediated by lipopolysaccharide (LPS) modification, which is regulated by the two-component system, PhoP/PhoQ. Yersinia enterocolitica is a common foodborne pathogen. However, PhoP/PhoQ has not been thoroughly studied in Y. enterocolitica. In this study, the functions of PhoP/PhoQ in Y. enterocolitica intrinsic resistance was investigated. The survival rate of Y. enterocolitica was found to decrease with the deletion of PhoP/PhoQ. Further, PhoP/PhoQ was found to play an important role in maintaining membrane permeability, intercellular metabolism and reducing membrane depolarization. Based on subsequent studies, the binding ability of polymyxin to Y. enterocolitica was decreased by the modification of LPS with structures, such as L-Ara4N and palmitate. Analysis of the gene transcription levels revealed that the LPS modification genes, pagP and arn operon, were downregulated with the deletion of PhoP/PhoQ in Y. enterocolitica during exposure to polymyxin. In addition, pmrA, pmrB, and eptA were downregulated in the mutants compared with the wild-type strain. Such findings demonstrate that PhoP/PhoQ contributes to the intrinsic resistance of Y. enterocolitica toward polymyxins. LPS modification with L-Ara4N or palmitate is mainly responsible for the resistance of Y. enterocolitica to polymyxins. The transcription of genes related to LPS modification and PmrA/PmrB can be both affected by PhoP/PhoQ in Y. enterocolitica. This study adds to current knowledge regarding the intrinsic resistance of Y. enterocolitica to polymyxin and the role of PhoP/PhoQ in Enterobacteriaceae.